Corruption and combating corruption in transitional societies: example of Croatia and Serbia - Božić, Vanda B.; Nikač, Željko V. (Sociološki pregled, 2018)
Today corruption is a global issue and one of the greatest threats to the democratic state order and the rule of law. The paper points to the criminological and legal aspects of corruption in Croatia and Serbia as countries that have somewhat completed the transition process, society reform and harmonization of legislation with relevant international documents. Provided are the most significant international and national legislative sources that are important for the suppression of corruption, as well as the mechanisms for monitoring the presence of corruption in these countries. A study of the state and movements of corrupt criminal offenses committed in Croatia and Serbia was conducted and their comparative representation was given. Distinctions in the incrimination of corruptive offenses in these countries were pointed out, which are, among other things, the result of the absence of a single international definition of corruption. Concluding considerations include the de lege ferenda proposals with the aim of more effective combating of corruption in the public as well as in the private sector.Keywords: corruption, corrupt criminal oﬀenses, transition, Croatia, Serbia.